Introducing a Hydrogen‐Bond Donor into a Weakly Nucleophilic Brønsted Base: Alkali Metal Hexamethyldisilazides (MHMDS, M=Li, Na, K, Rb and Cs) with Ammonia. Issue 35 (26th July 2016) - Neufeld, Roman; Michel, Reent; Herbst‐Irmer, Regine; Schöne, Ralf; Stalke, Dietmar
Abstract: Alkali metal 1, 1, 1, 3, 3, 3‐hexamethyldisilazide (MHMDSs) are one of the most utilised weakly nucleophilic Brønsted bases in synthetic chemistry and especially in natural product synthesis. Like lithium organics, they aggregate depending on the employed donor solvents. Thus, they show different reactivity and selectivity as a function of their aggregation and solvation state. To date, monomeric LiHMDS with monodentate donor bases was only characterised in solution. Since the first preparation of LiHMDS in 1959 by Wannagat and Niederprüm, all efforts to crystallise monomeric LiHMDS in the absence of chelating ligands failed. Herein, we present ammonia adducts of LiHMDS, NaHMDS, KHMDS, RbHMDS and CsHMDS with unprecedented aggregation motifs: 1) The hitherto missing monomeric key compound in the LiHMDS aggregation architectures. Monomeric crystal structures of trisolvated LiHMDS (1 ) and NaHMDS (2 ), showing unique intermolecular hydrogen bonds, 2) the unprecedented tetrasolvated KHMDS (3 ) and RbHMDS (4 ) dimers and 3) the disolvated CsHMDS (5 ) dimer with very close intermolecular Si−CH3 ⋅⋅⋅Cs s‐block "agostic" interactions have been prepared and characterised by single‐crystal X‐ray structure analysis. Abstract : Finally monomeric : The hitherto missing key compounds in alkali metal 1, 1, 1, 3, 3, 3‐hexamethyldisilazide (MHMDS) aggregation are obtained from ammonia. The monomeric trisolvated LiHMDS (see figure) and NaHMDS show unique intermolecular hydrogen bonds. The KHMDS and RbHMDS dimers are tetrasolvated, whereas the CsHMDS dimer is only disolvated, compensating with very close intra‐ and intermolecular Si−CH3 ⋅⋅⋅Cs interactions.